2013
DOI: 10.1530/eje-13-0431
|View full text |Cite
|
Sign up to set email alerts
|

The cytologic category of oncocytic (Hurthle) cell neoplasm mostly includes low-risk lesions at histology: an institutional experience

Abstract: Design: The cytological diagnosis of oncocytic/Hurthle cell neoplasms (OCN) represents a challenge with which cytopathologists face up to in their practice. The majority of these lesions undergo surgery for a definitive characterization of the nature mainly due to their more aggressive behavior than other malignant follicular lesions. In this study, we aimed at the evaluation of the effective malignant rate in a large cohort of OCNs. Methods: From January 2008 to December 2011, we analyzed 150 cyto-histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
(82 reference statements)
4
17
0
Order By: Relevance
“…By comparing both calculated malignancy rates, the AUS‐NA subcategory revealed a substantially higher rate of malignancy (40.7% of FNA cases; 97.1% of resected cases) than what has been previously reported for the AUS category, or those found in other AUS subcategories, especially AUS‐MF (4.8% of FNA cases; 22.2% of resected cases) and AUS‐HC (5% of FNA cases; 20% of resected cases). Recently, Rossi et al reported that oncocytic/Hürthle cell features on FNAC showed a low risk of malignancy, supporting the low malignancy rate in the AUS‐HC subcategory in this study . These findings can be partly explained by the fact that the relatively large number of cases were histologically confirmed in the subcategory of AUS‐NA (n=68, 31.5%) as compared with the subcategories of AUS‐MF and AUS‐HC (n=9, 20.9%; n=4, 20.0%, respectively).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…By comparing both calculated malignancy rates, the AUS‐NA subcategory revealed a substantially higher rate of malignancy (40.7% of FNA cases; 97.1% of resected cases) than what has been previously reported for the AUS category, or those found in other AUS subcategories, especially AUS‐MF (4.8% of FNA cases; 22.2% of resected cases) and AUS‐HC (5% of FNA cases; 20% of resected cases). Recently, Rossi et al reported that oncocytic/Hürthle cell features on FNAC showed a low risk of malignancy, supporting the low malignancy rate in the AUS‐HC subcategory in this study . These findings can be partly explained by the fact that the relatively large number of cases were histologically confirmed in the subcategory of AUS‐NA (n=68, 31.5%) as compared with the subcategories of AUS‐MF and AUS‐HC (n=9, 20.9%; n=4, 20.0%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Recently, Rossi et al reported that oncocytic/ H€ urthle cell features on FNAC showed a low risk of malignancy, supporting the low malignancy rate in the AUS-HC subcategory in this study. 21 These findings can be partly explained by the fact that the relatively large number of cases were histologically confirmed in the subcategory of AUS-NA (n568, 31.5%) as compared with the subcategories of AUS-MF and AUS-HC (n59, 20.9%; n54, 20.0%, respectively). Moreover, in Korea, PTCs comprise approximately 95% of thyroid cancer and 90% of PTCs are of classic type, whereas follicular carcinomas are very rare.…”
Section: Cancer Cytopathologymentioning
confidence: 94%
“…Reported malignancy rates for HC lesions diagnosed by FNAC vary between 5 and 45% [3, 5, 9, 17]. In the meta-analysis by Straccia et al [18], HC lesions categorized as FN/SFN resulted more frequently in benign lesions on histology (65%), and the rate of malignancy ranged between 14 and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The sonographic features of thyroid nodules have consistently failed to predict malignancy in FN with indeterminate cytology [13,14,22]. However, a hypoechoic appearance, the presence of microcalcifications (defined as < 2 mm hyperechoic spots), irregular or blurred margins, and intra-nodular vascularization are all taken as potential markers of malignancy, especially when present in combination [5,11,21].…”
Section: Discussionmentioning
confidence: 99%